A framework for improving school safety management: applying lean thinking to a case study in Thailand. (18th December 2014) - Srichai, Pachernwaat; Yodmongkol, Pitipong; Chakpitak, Nopasit; Meksamoot, Komsak; Sureephong, Pradorn
School safety is critical to education, but is rarely managed effectively. In Thailand, school safety is lower priority than other educational issues, lacking effective policy, and with schools struggling to justify safety costs. This paper outlines a novel application of lean thinking, which aims to control costs, bureaucracy and waste associated with managing school safety. A Thai primary school is the case study, where current safety is reviewed with regard to key aspects of management, including people, finance and operations. Lean thinking is applied to improve safety management and results show significant potential, along with management implications and future recommendations.